Pelaksanaan Kegiatan Kemasyarakatan Melalui Kuliah Kerja Lapangan di Dusun Airport - Hendra Bata; Sundari Sundari; Sitti Aisyah; Annisa Safitri; Asmaul Husna; Muh. Risman; Nurjanah Nurjanah; Qurotu Aeni Fatimah; Rahmat Ridwan; Siti Zulaiha; Yusnaeni Yusnaeni (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2023)
Problems of limited resources, limited funds, limited facilities, and people being less active in community activities are still often encountered. This service aims to increase awareness and experience for the community to participate in community activities. The method used is the participatory action research method. The result is that this service is carried out through several activity programs, namely: Teaching program at TPA, where with this activity program students can read the Al-Qur'an, memorize daily prayers such as short hadiths, as well as several short surahs. Students can also perform prayer movements, recite prayers, dhikr, and pray. Through the commemoration of Isra' Mi'raj, the community becomes united. The Clean Friday program has resulted in the habit of caring for the environment and providing trash cans. This healthy Saturday program results in gymnastics activities every Saturday morning and the establishment of friendship between residents by exercising together. Next, the weekly recitation program resulted in masjelis taklim recitation activities, which were carried out with the women, and the establishment of friendship between residents of Dusun Airport. Lastly, there is the mosque rehabilitation program, which resulted in the provision of cleaning equipment for the mosque, the availability of several hundred pieces of paper for road repairs in the mosque yard, and the provision of cupboard tables.